Kinetic and thermodynamic equilibrium of asphaltenes sorption onto formation rock: evaluation of the wash in the adsorptive properties (2012)
The main objective was to obtain kinetic and thermodynamic equilibrium of asphaltene sorption onto powder ROCK obtained from the Guadalupe formation (washed and unwashed) at different times, temperatures and concentrations. However, the effect of temperature in the equilibrium sorption is not significant. Rock powders were characterized by N2 sorption at -196°C. Equilibrium sorption of asphaltenes in rock powders, within a range of concentrations from 250 to 1500 ppm, was determined using a static method. Sorption curves show Type I behavior, according to IUPAC. Langmuir model was used for computing the monolayer asphaltene content values for the sorption at different temperatures, showing a good fit respect to the experimental data. Sorption kinetics of asphaltenes in rock samples is function of the concentration and for concentrations of 1500 ppm equilibrium is reached about 90 min. Pseudo first order and pseudo second order kinetic models were applied to the experimental data for the different concentrations for the two rock samples with a better result for the pseudo-first order kinetic model. The washing effect on the equilibrium was not significant; however the adsorptive capacity of the rock without washing was slightly higher than the rock washed with n-heptane and toluene.